2023
DOI: 10.2334/josnusd.22-0396
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic preferences of orthodontists, dentists, and plastic surgeons for balanced facial profiles

Abstract: Purpose:The aim of this investigation was to determine whether the facial esthetics of subjects rated as "attractive" can be related to specific cephalometric soft tissue parameters. Methods: The profile silhouettes of 100 subjects (45 males and 55 females) were rated by 60 esthetics specialists (20 orthodontists, 20 dentists, and 20 plastic surgeons) using a Likert scale, and 30 of the subjects were selected as being "attractive". The cephalometric measurements of the attractive group were then compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In contrast, young undergraduate students tend to prefer slightly protrusive lip positions [ 32 ]. Milutinovic et al [ 4 ] have observed that orthodontists, dentists, and plastic surgeons commonly hold the belief that a more prominent lip and a more symmetrical facial profile are regarded as the most visually appealing facial attributes. However, a study conducted on the Korean population revealed that those with protruding profiles were assigned lower ratings, whilst those with retruded profiles were favoured [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, young undergraduate students tend to prefer slightly protrusive lip positions [ 32 ]. Milutinovic et al [ 4 ] have observed that orthodontists, dentists, and plastic surgeons commonly hold the belief that a more prominent lip and a more symmetrical facial profile are regarded as the most visually appealing facial attributes. However, a study conducted on the Korean population revealed that those with protruding profiles were assigned lower ratings, whilst those with retruded profiles were favoured [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current society has shown significant interest in the aesthetic perception of the face, irrespective of its structural or functional aspects. It has been shown that individuals seeking orthodontic treatment are predominantly driven by their own self-perception of dentofacial esthetics [ 1 4 ]. One of the primary factors motivating individuals to get orthodontic evaluation is their subjective perception of their dentofacial aesthetics, which also exerts a substantial influence on their treatment expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing facial and dental structures is crucial for achieving successful esthetic prosthodontic treatments. A Two-Dimensional (2D) esthetic analysis utilizing facial and dental photographs has been introduced to ensure predictable esthetic outcomes [1][2][3][4]. This analysis involves importing full-face photographs taken in a relaxed state, during a wide smile, and smartphone video editing software that supports the smile design for an esthetic treatment plan [5].…”
Section: Introductionmentioning
confidence: 99%